TEKNOLOGI EKSISTING USAHA TERNAK SAPI KELOMPOK TANI KARYA BERSAMA PADA PENDAMPINGAN PENGEMBANGAN KAWASAN PETERNAKAN KABUPATEN JAYAPURA - Petrus Alexander Beding; Batseba M.W. Tiro; Ghalih P Dominanto (Universitas Sebelas Maret, 2020)
Jayapura is one of regencies in Papua which is designated as development of breeding area of beef cattle commodities. This study aims to present data and information about the profile of beef cattle farms in the Karya Bersama Farmer Group, Namblong district, Jayapura regency as the location for assisting the development of breeding area of beef cattle commodities. Data collection were conducted by survey and interview to 24 farmers at Kelompok Tani Karya Bersama that strengthened by Focus Group Discussion. The demonstration plot was carried out by introducing forage processing technology into silage and fermented straw as well as additional feed (bran) and observing the level of livestock reproduction. The results showed that the level of productivity of cattle is still relatively low, where calving interval is long (18-24 months), high S/C value (2 - 4), low birth weight (15-18 kg) and changes in body weight 0.1-0.2 kg/head/day. However, the assistance of technology can improve the productivity of cattle.